A Clinical Expert System For Positional Vertigo (International Journal of Engineering and Computer Science, 2013)
Vertigo, dizziness and balance-related conditions are among the most common health problems in adults. The centers for Disease Control and Prevention estimate that 7.4 Million per year visit a doctor for vertigo or dizziness. Almost everyone in their life will have a balance problem in mild or in severe. Positioning of any image throws ear, proprioceptor and eye- these will take signal to brain. If anyone mistakes leads to vertigo. Positional Vertigo may also be caused by inflammation within the inner ear (labyrinthitis or vestibular neuritis), which is characterized by the sudden onset of vertigo and may be associated with hearing loss. The severity of the problem can be identified with the knowledge based system that intern uses domain specific knowledge leads to develop an Expert system. This expert system will analyses the details of the patient through the software based questionnaire and checks the severity of the problem and suggests suitable cognitive and behavioral therapies to mitigate the problem of vertigo. The expert system also suggests suitable rehabilitation exercises and diet in considering usage, duration, precautions based on the case and the severity and develops a comprehensive response, which can be used as supplement to the doctor.